Fatal Hepatocellular Carcinoma in a Patient with Occult Hepatitis B Virus Infection following the Administration of R-CHOP for Diffuse Large B-Cell Lymphoma - Pitini, Vincenzo; Rizzo, Massimo; Arrigo, Carmela; Mondello, Patrizia; Altavilla, Giuseppe (Case Reports in Hematology, 2012)
Occult hepatitis B (OBI) is caused by a persistent low-level replication of HBV. Like overt HBV infection, OBI can be associated with the integration of HBV sequences into the host genome and has a substantial clinical relevance for patients who are severely immunosuppressed for long durations. We present the case of a patient with a diffuse large B-cell non-Hodgkin lymphoma and OBI who developed a hepatocellular carcinoma with a fulminant clinical course following the administration of rituximab plus CHOP.